Psychophysiological Effects of Left-Hand Contractions on Golf-Putting and Dart-Throwing Performance. - Mizuno, Kanta; Masaki, Hiroaki (Journal of Sport & Exercise Psychology, 2025)
Left-hand contractions (LHCs) are considered a useful technique to facilitate athletic performance under pressure by inhibiting conscious motor control through the induction of hemispheric brain asymmetry. However, the underlying mechanisms of LHCs remain unclear. Two experiments were conducted: novice golfers (30 participants) and dart players (40 participants) completed tasks while their cortical, muscle, and cardiac activities and kinematics were recorded. Performance was measured as the distance from the target. In Study 1 (golfers), no differences in performance were observed; however, LHCs reduced the electromyography signals in the left forearm during golf putting. In Study 2 (dart players), performance did not differ between study groups. Although right-dominant hemispheric asymmetry was induced by LHCs, it may not have facilitated golf-putting and dart-throwing performances. As LHCs induced asymmetry only around the central and parietal sites, we cast doubt on the idea that LHCs inhibit the conscious processing of movements due to left-temporal activation.